Analisis Pengetahuan Pencegahan Covid-19 Pada Masyarakat Berdasarkan Perceived Susceptibility, Perceived Severity, Perceived Benefits, dan Perceived Barriers - Sulistyo, Raysandi Anggit; Sulistyowati, Muji (Universitas Airlangga, 2024)
Background: In Indonesia as of September 30, 2022, the total number of Covid-19 positive patients was 6,431,624 people, with 158,112 patients dying. However, there are still many people who still lack knowledge and attitudes regarding the dangers of exposure to the Covid-19 virus on health. Therefore, the purpose of this study is to analyze the relationship between knowledge and community behavior in efforts to prevent Covid-19, especially in Pondok Maritim Indah, Kelurahan Balas Klumprik, Kecamatan Wiyung, Surabaya. Objectives: Determine the relationship between perceived susceptibility, perceived severity, perceived benefit, perceived barriers. with Covid-19 prevention behavior. Methods: This type of research is an analytical observational study with a cross sectional design. The sample size of this study was 95 people, taken from the entire community of RW 06 Pondok Maritim Indah, Kelurahan Balas Klumprik, Kecamatan Wiyung, Surabaya. Data collection was carried out using a questionnaire containing 7 statements of perceived susceptibility, 7 statements of perceived severity, 7 statements of perceived benefit, 7 statements of perceived barriers, and 7 statements of self-efficacy. The data analysis technique uses univariate analysis to describe data per variable and bivariate analysis to determine the relationship between two variables. Bivariate analysis uses chi-square test. Result: Results showed that there was a relationship between public knowledge about preventing Covid-19 and all the perceptions studied, starting from perceptions of vulnerability (p=0.000; OR=6.692), perceptions of severity (p=0.000; OR=4.833), perceptions of benefit (p=0.000; OR=1.586)), perceptions of barriers (p=0.000; OR=10.875). Conclusions: The conclusion of the study is that perceptions of vulnerability, perceived severity, perceived benefits, perceived barriers, are related to people's knowledge about Covid-19 prevention. Perceived obstacles are the most dominant perceptions related to public knowledge about Covid-19 prevention. Therefore, the role of community leaders is needed to always provide advice and support to the surrounding community to maintain and implement health protocols.